A 117‐year long index of the Pacific‐Japan pattern with application to interdecadal variability. (29th July 2015) - Kubota, Hisayuki; Kosaka, Yu; Xie, Shang‐Ping
ABSTRACT: The Pacific‐Japan (PJ) pattern affects interannual variability in the East Asian and western North Pacific (WNP) summer monsoons. This teleconnection pattern is characterized by a meridional dipole of anomalous circulation and precipitation between the tropical WNP and the midlatitudes. This study develops a long index of the PJ pattern using station‐based atmospheric pressure data to track the PJ variability from 1897 to 2013. This index is correlated with a wide array of climate variables including air temperature, precipitation, Yangtze River flow, Japanese rice yield and the occurrence of tropical cyclones over the WNP (especially those that make landfall on the Chinese and Korean coast). For the recent three decades, the PJ index reproduces well‐known correlations with El Niño‐Southern Oscillation (ENSO) in the preceding boreal winter and Indian Ocean temperature in the concurrent summer. For the 117‐year period, this ENSO‐PJ relationship varies on interdecadal time scales, with low correlations in the 1920s and from the 1940s to 1970s, and recurrences of significant correlations at the beginning of the 20th century and the 1930s. In accordance with the modulation, the magnitude and regional climate effect of the PJ variability have changed. These results highlight the importance of interdecadal modulations of climate anomalies in the summer WNP and the need of long‐term observations to study such modulations.